2022
DOI: 10.1186/s40779-022-00417-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in the pathogenesis and treatment of acute lung injury

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are common life-threatening lung diseases associated with acute and severe inflammation. Both have high mortality rates, and despite decades of research on clinical ALI/ARDS, there are no effective therapeutic strategies. Disruption of alveolar-capillary barrier integrity or activation of inflammatory responses leads to lung inflammation and injury. Recently, studies on the role of extracellular vesicles (EVs) in regulating normal and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 148 publications
(214 reference statements)
0
49
0
Order By: Relevance
“…10−12 Recently, some novel therapies, such as mesenchymal stem cells, targeting inflammatory storms by novel proteins, have attracted attention to reduce lung injury. 13,14 Thus, further treatments involving novel mechanisms to improve the overall survival rate are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10−12 Recently, some novel therapies, such as mesenchymal stem cells, targeting inflammatory storms by novel proteins, have attracted attention to reduce lung injury. 13,14 Thus, further treatments involving novel mechanisms to improve the overall survival rate are required.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that corticosteroids can reduce the mortality of ALI/ARDS in the intensive care unit (ICU) patients, but severe side effects cannot be avoided . The therapies, such as antioxidants, ketoconazole, and exogenous surfactants, exhibited promising clinical outcomes in animal models, whereas they have not realized clinical transformation. Recently, some novel therapies, such as mesenchymal stem cells, targeting inflammatory storms by novel proteins, have attracted attention to reduce lung injury. , Thus, further treatments involving novel mechanisms to improve the overall survival rate are required.…”
Section: Introductionmentioning
confidence: 99%
“…10 Damage to this barrier that results in increased alveolar permeability is a key characteristic of ALI, as this allows water, red blood cells, pro-inflammatory factors (e.g., reactive oxygen species [ROS] and tumor necrosis factor-α [TNFα]), and immune cells (e.g., neutrophils and monocytes) to freely enter and exit the alveoli, which promotes lung inflammation and dysfunction. 7,8,11 PMVECs that line vessels of the pulmonary circulatory system maintain their integrity and act as highly impermeable barriers that prevent the free passage of water, solutes, pathogens, and immune cells between the microvessels and the lung interstitium. 11,12 PMVEC dysfunction (e.g., abnormal proliferation, apoptosis, necrosis, or tight junction disruption) can disrupt this barrier and promote the development of ALI.…”
Section: Introductionmentioning
confidence: 99%
“…g ., reactive oxygen species [ROS] and tumor necrosis factor-α [TNFα]), and immune cells ( e . g ., neutrophils and monocytes) to freely enter and exit the alveoli, which promotes lung inflammation and dysfunction. ,, PMVECs that line vessels of the pulmonary circulatory system maintain their integrity and act as highly impermeable barriers that prevent the free passage of water, solutes, pathogens, and immune cells between the microvessels and the lung interstitium. , PMVEC dysfunction ( e . g ., abnormal proliferation, apoptosis, necrosis, or tight junction disruption) can disrupt this barrier and promote the development of ALI. , Restoring PMVEC barrier integrity or preventing its disruption is thus a good means to treat ALI caused by dysregulation of endogenous cytokines ( e .…”
Section: Introductionmentioning
confidence: 99%
“…EVs from different sources can contain pro- or anti-inflammatory factors, regulating different kinds of alveolar cells, including epithelial cells, endothelial cells, macrophages, and neutrophils. 8 Although the characterization of sEV-CC16 is well described, the immortalized cell source is not recommended for clinical therapy. Moreover, the sEV-control did not exhibit therapeutic effects, suggesting that sEVs themselves did not act as a functional factor.…”
mentioning
confidence: 99%